Diazepam effect during early neonatal development correlates with neuronal Cl−. Issue 12 (27th October 2015) - Glykys, Joseph; Staley, Kevin J.
Abstract: Objective: Although benzodiazepines and other GABAA receptors allosteric modulators are used to treat neonatal seizures, their efficacy may derive from actions on subcortical structures. Side effects of benzodiazepines in nonseizing human neonates include myoclonus, seizures, and abnormal movements. Excitatory actions of GABA may underlie both side effects and reduced anticonvulsant activity of benzodiazepines. Neocortical organotypic slice cultures were used to study: (1) spontaneous cortical epileptiform activity during early development; (2) developmental changes in [Cl − ]i and (3) whether diazepam's anticonvulsant effect correlated with neuronal [Cl − ]i . Methods: Epileptiform activity in neocortical organotypic slice cultures was measured by field potential recordings. Cl − changes during development were assessed by multiphoton imaging of neurons transgenically expressing a Cl‐sensitive fluorophore. Clinically relevant concentrations of diazepam were used to test the anticonvulsant effectiveness at ages corresponding to premature neonates through early infancy. Results: (1) Neocortical organotypic slices at days in vitro 5 (DIV5) exhibited spontaneous epileptiform activity. (2) Epileptiform event duration decreased with age. (3) There was a progressive decrease in [Cl − ]i over the same age range. (4) Diazepam was ineffective in decreasing epileptiform activity at DIV5‐6, but progressively more effective at older ages through DIV15. (5) At DIV5‐6, diazepam worsened epileptiform activity in 50% of the slices. Interpretation: The neocortical organotypic slice is a useful model to study spontaneous epileptiform activity. Decreasing [Cl − ]i during development correlates with decreasing duration of spontaneous epileptiform activity and increasing anticonvulsant efficacy of diazepam. We provide a potential explanation for the reports of seizures and myoclonus induction by benzodiazepines in newborn human neonates and the limited electrographic efficacy of benzodiazepines for the treatment of neonatal seizures.